STRENGTHENING MANAGEMENT INFORMATION SYSTEMS IN IMPROVING THE PERFORMANCE OF ADMINISTRATIVE STAFF - Nuryadin, Rusmin; Aminah, Aminah; Ilyas, Mohd (Jurnal As-Salam, 2025)
Management Information Systems (MIS) play a vital role in optimizing administrative operations in education, including at MTsN 2 Bireuen. The effective implementation of MIS can significantly improve administrative staff performance. This study aims to analyze the management of MIS and its impact on the performance of administrative staff at MTsN 2 Bireuen, focusing on the aspects of planning, organizing, implementation, and evaluation. This qualitative research used open interviews, observation, and documentation for data collection that involved the headmaster, head of administrative affairs, 6 administrative employees, and 3 teachers at MTsN 2 Bireuen. Data analysis techniques included data reduction, presentation, and verification. The results indicate: (1) Planning: The MIS planning is well-executed, with clear goal setting, assessments, and alternative evaluations. (2) Organizing: The organizing process is effective, with clear task delegation, coordination, and organizational structure. (3) Implementation: Implementation involves communication, motivation, leadership, and alignment of goals. (4) Evaluating: Evaluating includes performance measurement, corrective actions, and feedback for process improvements. The management of MIS at MTsN 2 Bireuen positively affects administrative staff performance, with good implementation across all stages. This study provides insights for other educational institutions on developing effective MIS to enhance administrative efficiency and effectiveness, with recommendations for continuous improvement.